Transcript Profiling Identifies Gene Cohorts Controlled by Each Signal Regulating Trans-Differentiation of Epidermal Cells of Vicia faba Cotyledons to a Transfer Cell Phenotype - Zhang, Hui-Ming; Wheeler, Simon L.; Xia, Xue; Colyvas, Kim; Offler, Christina E.; Patrick, John W. (Frontiers in Plant Science, 2017)
Transfer cells (TCs) support high rates of membrane transport of nutrients conferred by a plasma membrane area amplified by lining a wall labyrinth comprised of an uniform wall layer (UWL) upon which intricate wall ingrowth (WI) papillae are deposited. A signal cascade of auxin, ethylene, extracellular hydrogen peroxide (H2O2) and cytosolic Ca2+ regulates wall labyrinth assembly. To identify gene cohorts regulated by each signal, a RNA- sequencing study was undertaken using Vicia faba cotyledons. When cotyledons are placed in culture, their adaxial epidermal cells spontaneously undergo trans-differentiation to epidermal TCs (ETCs). Expressed genes encoding proteins central to wall labyrinth formation (signalling, intracellular organization, cell wall) and TC function of nutrient transport were assembled. Transcriptional profiles identified 9,742 annotated ETC-specific differentially expressed genes (DEGs; Log2fold change >1; FDR p ≤0.05) of which 1,371 belonged to signalling (50%), intracellular organization (27%), cell wall (15%) and nutrient transporters (9%) functional categories. Expression levels of 941 ETC-specific DEGs were found to be sensitive to the known signals regulating ETC trans-differentiation. Significantly, signals acting alone, or in various combinations, impacted similar numbers of ETC-specific DEGs across the four functional gene categories. Amongst the signals acting alone, H2O2 exerted most influence affecting expression levels of 56% of the ETC-specific DEGs followed by Ca2+ (21%), auxin (18%) and ethylene (5%). The dominance by H2O2 was evident across all functional categories, but became more attenuated once trans-differentiation transitioned into WI papillae formation. Amongst the eleven signal combinations, H2O2/Ca2+ elicited the greatest impact across all functional categories accounting for 20% of the ETC-specific DEG cohort. The relative influence of the other signals acting alone, or in various combinations, varied across the four functional categories and two phases of wall labyrinth construction These transcriptome data provide a powerful information platform from which to examine signal transduction pathways and how these regulate expression of genes encoding proteins engaged in intracellular organization, cell wall construction and nutrient transport.